AN ANALYSIS OF CODE MIXING IN A BILINGUAL LANGUAGE ACQUISITION - Yudhie Indra Gunawan; Suparti - - (Universitas Muhammadiyah Tangerang, 2018)
AbstractIn studies of bilingual language acquisition, code-mixing refers to a developmental stage during which children mix elements of more than one language. Nearly all bilingual children go through a period in which they move from one language to another without apparent discrimination. This differs from code-switching, which is understood as the socially and grammatically appropriate use of multiple varieties. Whether we aware or not, in daily life conversation children under 4 years old who live in a bilingual family often produce utterances that combine elements of both (or all) of their developing languages. Some linguists suggest that this code-mixing reflects a lack of control or ability to differentiate the languages. Others argue that it is a product of limited vocabulary; very young children may know a word in one language but not in another.This study looks closely at code- mixing in early bilingualism of Javanese and Bahasa Indonesia. The name of the subject is Thomas Maulana, he is 4 years old. From birth, he has been addressed with two languages by his family members. Thomas’ parents used Javanese as their first language in their home and they used Bahasa Indonesia as their second language to communicate in their environment. From the data, estimation of exposures of the two languages towards Thomas at home was calculated. The most used language at home is 80% Javanese and the least is 20% Bahasa Indonesia.Based on the data collected, the researcher got the result that the use of two languages in a bilingual language acquisition gives influence towards Thomas language development. As the researcher observed Thomas produced more mixed language sentence in his daily conversation, especially when he has conversation in Bahasa Indonesia. He tends to mix more language when he speaks in Bahasa Indonesia than when he speaks in Javanese. As shown in the data that the most used language at home is 80% Javanese and the least is 20% Bahasa Indonesia. It is clear that the use of Javanese in Thomas’ language sentence was more dominant than Bahasa Indonesia.Keywords: Code Mixing, Bilingual, Language Acquisition